Triple-phase ceramic 2D nanocomposite with enhanced thermoelectric properties. Issue 4 (April 2019) - Bittner, Michael; Kanas, Nikola; Hinterding, Richard; Steinbach, Frank; Groeneveld, Dennis; Wemhoff, Piotr; Wiik, Kjell; Einarsrud, Mari-Ann; Feldhoff, Armin
Abstract: A thermoelectric triple-phase p-type Ca3 Co4 O9 -Na x CoO2 -Bi2 Ca2 Co2 O9 (CCO–NCO–BCCO) 2D nanocomposite was obtained from pressureless sintering in air. The anisotropic thermoelectric properties of the nanocomposite exhibit a high electrical conductivity of 116 S cm −1 and a power factor of 6.5 μW cm −1  K −2 perpendicular to the pressing direction at 1073 K in air. A corresponding zT value of 0.35 was obtained. Three co-doped, thermoelectrically active misfit-layered materials were stacked to form a triple-phase nanocomposite, which combines the advantages of all three materials. The resulting nanocomposite enables simultaneous increases of the isothermal electrical conductivity σ and the Seebeck coefficient α by charge carrier concentration engineering and synergistic effects. The Bi2 Ca2 Co2 O9 and Na x CoO2 phases were stabilized in a Ca3 Co4 O9 matrix at high temperatures. To evaluate the application of the nanocomposite in high-temperature thermoelectric generators, the representation of the electrical conductivity and power factor in a Ioffe plot was more appropriate than the zT value.